Too Late to Be Grounded? Motor Resonance for Action Words Acquired After Middle Childhood - Muñoz-Arias, E (Academic Press, 2020)
Though well established for languages acquired in infancy, the role of embodied mechanisms remains poorly understood for languages learned in middle childhood and adulthood. To bridge this gap, we examined 34 experiments that assessed sensorimotor resonance during processing of action-related words in real and artificial languages acquired since age 7 and into adulthood. Evidence from late bilinguals indicates that foreign-language action words modulate neural activity in motor circuits and predictably facilitate or delay physical movements (even in an effector-specific fashion), with outcomes that prove partly sensitive to language proficiency. Also, data from newly learned vocabularies suggest that embodied effects emerge after brief periods of adult language exposure, remain stable through time, and hinge on the performance of bodily movements (and, seemingly, on action observation, too). In sum, our work shows that infant language exposure is not indispensable for the recruitment of embodied mechanisms during language processing, a finding that carries non-trivial theoretical, pedagogical, and clinical implications for neurolinguistics, in general, and bilingualism research, in particular. © 2019 Elsevier Inc.